Bacteria in Cancer Therapeutics: A Framework for Effective Therapeutic Bacterial Screening and Identification - Ashu, Eta E. (J Cancer, 2019)
By 2030, the global incidence of cancer is expected to increase by approximately 50%. However, most conventional therapies still lack cancer selectivity, which can have severe unintended side effects on healthy body tissue. Despite being an unconventional and contentious therapy, the last two decades have seen a significant renaissance of bacterium-mediated cancer therapy (BMCT). Although promising, most present-day therapeutic bacterial candidates have not shown satisfactory efficacy, effectiveness, or safety. Furthermore, therapeutic bacterial candidates are available to only a few of the approximately 200 existing cancer types. Excitingly, the recent surge in BMCT has piqued the interest of non-BMCT microbiologists. To help advance these interests, in this paper we reviewed important aspects of cancer, present-day cancer treatments, and historical aspects of BMCT. Here, we provided a four-step framework that can be used in screening and identifying bacteria with cancer therapeutic potential, including those that are uncultivable. Systematic methodologies such as the ones suggested here could prove valuable to new BMCT researchers, including experienced non-BMCT researchers in possession of extensive knowledge and resources of bacterial genomics. Lastly, our analyses highlight the need to establish and standardize quantitative methods that can be used to identify and compare bacteria with important cancer therapeutic traits.